2021
DOI: 10.1029/2021jd034534
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Organic Aerosol From Wood Smoke Influenced by Burning Phase and Solar Radiation

Abstract: Biomass burning emissions are the most important contributors to the global carbonaceous aerosols in the atmosphere, leading to important climate and human health impacts (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 102 publications
(165 reference statements)
0
8
0
Order By: Relevance
“…Ammonium nitrate particles were used to calibrate the ionization efficiency (IE) in AMS following the standard protocol. The HR-ToF-AMS was operated with a collection efficiency (CE) of 0.5 and 1 min sampling time resolution. Elemental ratios (O/C, H/C) of organics were performed using the updated improved-ambient (IA) method as proposed by Canagaratna et al Organic ions were classified as hydrocarbons (C x H y + ) and fragments containing different numbers of oxygen (C x H y O 1 + , C x H y O 2 + , C x H y O 3 + ) and containing nitrogen are classified as containing (C x H y O z N p + ) or without oxygen (C x H y N p + ) and defined as N-fragments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ammonium nitrate particles were used to calibrate the ionization efficiency (IE) in AMS following the standard protocol. The HR-ToF-AMS was operated with a collection efficiency (CE) of 0.5 and 1 min sampling time resolution. Elemental ratios (O/C, H/C) of organics were performed using the updated improved-ambient (IA) method as proposed by Canagaratna et al Organic ions were classified as hydrocarbons (C x H y + ) and fragments containing different numbers of oxygen (C x H y O 1 + , C x H y O 2 + , C x H y O 3 + ) and containing nitrogen are classified as containing (C x H y O z N p + ) or without oxygen (C x H y N p + ) and defined as N-fragments.…”
Section: Methodsmentioning
confidence: 99%
“…The HR-ToF-AMS was operated with a collection efficiency (CE) of 0.5 and 1 min sampling time resolution. Elemental ratios (O/C, H/C) of organics were performed using the updated improved-ambient (IA) method as proposed by Canagaratna et al Organic ions were classified as hydrocarbons (C x H y + ) and fragments containing different numbers of oxygen (C x H y O 1 + , C x H y O 2 + , C x H y O 3 + ) and containing nitrogen are classified as containing (C x H y O z N p + ) or without oxygen (C x H y N p + ) and defined as N-fragments. We aim to broadly (but not quantitively) identify the contribution of nitrogen-containing OA (NOCs) from the bulk OA, hereby using several N-containing ions including CN + , CNO + , CH 3 NO + , C 3 H 4 N + , C 3 H 5 N + , C 2 H 2 NO + , C 3 H 6 N + , C 2 H 3 NO + , C 3 H 7 N + , C 3 H 8 N + , C 2 H 5 NO + , and C 2 H 6 NO + ( f CxHyNp+CxHyNpOz ) as the main fragments in determining the fraction of NOCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical transport of aerosol and gases in the planetary boundary layer (PBL) from the surface to the lower free troposphere (FT) importantly determines the influence of anthropogenic emissions to the upper level of the atmosphere; for example, aerosols in the upper level of the PBL may have more important feedback effects in influencing the boundary layer dynamics (Li et al, 2017). The aerosol could be upward transported from surface to upper level through daytime convective mixing in the PBL (Garratt, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Smoldering emissions were rich in carbonaceous peaks. The flaming phase generally produced organic aerosols of higher light absorptivity, while the light scattering particles dominated in the smoldering phase. , It suggested that the particles emitted under different burning conditions should be treated separately in climate modeling . Representative particles versus total single particles are given in Figure S3.…”
Section: Resultsmentioning
confidence: 99%